Making Room for Smallholder Cooperatives in Tanzanian Tea Production: Can Fairtrade Do That? - Loconto, Allison Marie (Journal of business ethics, 2012)
The objective of this article is to examine the different ways that smallholders are brought into Fairtrade certification schemes in the Tanzanian tea industry. We examine the different ownership relations of processing factories and the perceived benefits of these different arrangements. We use descriptive qualitative analysis based on qualitative interviews and focus groups conducted between 2008 and 2010 to identify the significance between factory ownership organization and Fairtrade certification. We find that there is a movement toward innovation in the organizational strategies, which includes new ownership arrangements of processing factories and outgrower contracts that have been associated with certified Fairtrade production. We also suggest that organizational innovation is significant for obtaining scheme success yet perceived benefits of and increased information about Fairtrade production is independent from ownership shares in processing.